Behavior Multigenerational Comparative Study: Eco-Fashion Purchase Behavior - Fathie Busyra; Ghassani Nayaka; Vidanicka Marthensz; Ina Agustini Murwani (Budapest International Research and Critics University, 2022)
Ecological impact and environmental sustainability in commerce has been a growing concern among both governments and consumers across geographies and industries. Fashion industry is one of the sectors getting pressure to change from both regulators and consumers. As consumer’s environmental awareness increases, so does the demand for eco-fashion all over the place, including Indonesia. Eco-label has become a tool for brands to communicate their commitment in sustainability. This study compares the green purchase behavior between generation X, Y and Z behavior in the eco-fashion market. The data was collected by an online survey distributed to generation X, Y and Z eco-fashion consumers. Data was analyzed by PLS-SEM and the Multi-Group Analysis (MGA). The result indicated that although behavior eco-label had influence on product attribute and perceived consumer effectiveness, both product attributes and environmental attitudes do not have a statistically significant effect on ecological affection. This study also showed that behavior generations X, Y, and Z had no significant differences in eco-fashion green purchase behavior.